Graph-based analysis of the correlation between mobility and telecommunication - Tajabad, Roya Esmaeili (Geodetski vestnik, 2023)
Considering the relationship between human movement patterns and telecommunications in space and cyberspace helps us better understand these movement patterns. This study investigated the relationship between human movement patterns and telecommunications using a graph structure. The parameters of the created graphs, including the node, edge, percentage of the loop’s total weights, weighted local clustering, and weighted global clustering coefficient were calculated and compared by a correlation matrix. Then, the effects of distance and the number of unique telecom partners were examined. Implementation of the proposed method on Mobile Data Challenge (MDC) data showed that the more the movement between two specific regions, the more the telecommunication exchanged. Furthermore, the ratio of the number of calls to the number of displacements increases slightly with increasing the distance between the origin and destination. The more telecom partners an individual has, the greater the number of displacements and the greater the number of regions that he visits. A person with less telecommunication with nearby areas also has less movement within nearby regions. Finally, the structure of movement and telecom graphs of an individual are similar—the higher the interaction and connections between nodes of the one, the more the connections between the nodes of the other.
Keywords: analiza grafov; človeško gibanje; graph analysis; human mobility; telecommunication; telekomunikacije